Analisis Kinerja Pegawai Puskesmas Kebayakan Kabupaten Aceh Tengah Berdasarkan Persepsi Pengguna Layanan - Yulianti, Defri; Aisyah, Siti; Khairani, Cut (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2024)
This study aims to analyze employee performance at the Kebayakan Health Center and the factors that influence it, as well as what efforts are made to improve employee performance. This research uses qualitative methods, with a total sample of 100 people consisting of 10 health center employees, 10 patients, and 80 people from the Kebayakan sub-district community. The results showed that the performance of Kebayakan Health Center employees based on productivity aspects and aspects of employee service quality was very good, responsiveness aspects still needed improvement to improve employee responsiveness, and responsibility aspects found that the community was satisfied with the performance of employees who were by applicable regulations, and accountability aspects were also considered to have provided satisfaction to the community. Factors that are very influential in improving employee performance are ability factors, where the work experience of employees who have handled patients for years and the placement of employees following their abilities and education can significantly improve performance. Meanwhile, the motivation factor was found to have less influence on improving employee performance. Furthermore, the efforts made to improve employee performance are examined from three factors: the providing expectations factor by providing medical service incentives that depend on the number of patient visits, the development factor by getting a promotion, and the communication factor through the supervisor.This study aims to analyze employee performance at the Kebayakan Health Center and the factors that influence it, as well as what efforts are made to improve employee performance. This research uses qualitative methods, with a total sample of 100 people consisting of 10 health center employees, 10 patients, and 80 people from the Kebayakan sub-district community. The results showed that the performance of Kebayakan Health Center employees based on productivity aspects and aspects of employee service quality was very good, responsiveness aspects still needed improvement to improve employee responsiveness, and responsibility aspects found that the community was satisfied with the performance of employees who were by applicable regulations, and accountability aspects were also considered to have provided satisfaction to the community. Factors that are very influential in improving employee performance are ability factors, where the work experience of employees who have handled patients for years and the placement of employees following their abilities and education can significantly improve performance. Meanwhile, the motivation factor was found to have less influence on improving employee performance. Furthermore, the efforts made to improve employee performance are examined from three factors: the providing expectations factor by providing medical service incentives that depend on the number of patient visits, the development factor by getting a promotion, and the communication factor through the supervisor.